2022
DOI: 10.3390/foods11223621
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality, Techno-Functional Characteristics, and Safety of Biomass Powder and Protein Isolate Produced from Penicillium maximae

Abstract: This study investigated the suitability of Penicillium maximae biomass powder and protein isolate as a food product or food ingredient. The biomass powder is rich in proteins (34.8%) and insoluble fiber (36.2%) but poor in lipids (3.1%). Strong water hydration (8.3 g/g, 8.5 g/g) and oil holding (6.9 g/g, 16.3 g/g) capacity were observed in the biomass powder and protein isolate, respectively, besides 100% emulsion stability, indicating multiple applications in the food industry. No locomotor impairment was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Protein hydrolysate showed a FC of 26.7% and a FS of 62% at pH 7, as presented in Table S1. Moura et al reported high FC (120%) and FS (91%) at pH 7 of protein isolate from Pencillium maximae fungal biomass. Protein isolate was obtained by alkaline extraction followed by isoelectric precipitation, and a relatively low yield of protein isolate was achieved (3.5% mass recovery).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein hydrolysate showed a FC of 26.7% and a FS of 62% at pH 7, as presented in Table S1. Moura et al reported high FC (120%) and FS (91%) at pH 7 of protein isolate from Pencillium maximae fungal biomass. Protein isolate was obtained by alkaline extraction followed by isoelectric precipitation, and a relatively low yield of protein isolate was achieved (3.5% mass recovery).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the fungal cell wall, rich in nondigestible polysaccharides, can be separated or disintegrated from the fungal cell to obtain a more concentrated extract of intracellular components such as amino acids, peptides, and nucleotides. , However, studies on the extraction of proteins for food applications from filamentous fungal biomass are scarce. Different treatments can be used to separate and recover fungal proteins from their cell-wall polysaccharides, such as alkaline extraction with isoelectric precipitation, alcohol–alkaline extraction, hydrolysis with proteolytic enzymes, and mechanical treatment . There is interest in the food industry to replace traditional chemical food additives with extracts from natural sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some research has been conducted on the potential of Penicillium biomass and protein isolate for food applications, it is not a mainstream or widely recognized meat alternative. Of note, a recent investigated the suitability of Penicillium maximae biomass powder and protein isolate for potential food applications (Moura et al., 2022). The biomass powder was found to be rich in proteins (34.8%) and insoluble fiber (36.2%), but low in lipids (3.1%).…”
Section: Health‐promoting Effects Of Mycoproteins: Strains Characteri...mentioning
confidence: 99%